Association between quality of life, menopausal status, and sociodemographic factors among middle-aged women in Iran. Issue 4 (December 2015) - Ghorbani, Raheb; Nassaji, Mohammad; Shahbazi, Akram; Rostami, Bemane; Taheri, Maryam
Abstract : Objective: Assessment of overall health, well-being, and quality of life (QoL) during middle age and menopause deserves special attention. The aim of this study was to investigate the effect of menopausal status and some sociodemographic variables on QoL among middle-aged women in Semnan, Iran. Participants and methods: This cross-sectional survey was conducted in 2012 in Semnan, Iran. The participants included 770 women aged 45–60 years. The data were collected by interview using a structured questionnaire that included sociodemographic characteristics, data on menopausal status, and QoL measurement using the Menopause-Specific Quality of Life questionnaire. Results: The mean±SD age of the women was 50.9±4.7 years. The overall unadjusted mean scores obtained for each domain were as follows: vasomotor: 1.83±1.86; psychosocial: 1.62±1.41; physical: 1.98±1.28; and sexual: 1.63±1.87. Logistic regression analysis showed that menopausal status was significantly associated with QoL in all domains, except the psychosocial domain. Age, BMI, household income, and number of children were significantly associated with impairment in QoL. Marital status, educational level, and residential area did not show any association with QoL in multivariate analysis. Conclusion and recommendations: Our findings confirm previous literature on the negative impact of menopausal symptoms on QoL, and show the interaction of some sociodemographic characteristics including age, number of children, household income, and BMI, on QoL. Health professionals should ensure that they consider a range of factors in middle-aged women's lives and provide insight into possible treatment strategies and lifestyle interventions for improving QoL.